A Diabetes Prevention Assessment Tool for American Indians - Christopher A. Taylor, PhD, RD; Kathryn S. Keim, PhD, RD; Dale R. Fuqua, PhD; Christine A. Johnson, PhD (Centers for Disease Control and Prevention, 2005)
Introduction American Indians have a disproportionately higher risk of developing type 2 diabetes. Few data are available about the perceptions of diabetes among American Indians, and no culturally appropriate tools are available for assessment of perceptions related to health and diabetes. Methods A diabetes prevention assessment tool was developed to measure perceptions of health and diabetes among American Indians. Predominant themes from qualitative interviews were used to develop the items for the tool. Data were collected at two autumn powwows, or intertribal dances, in Oklahoma. Reliability testing was performed using 185 surveys from American Indian adults not living on reservations. Principal axis factor analysis was performed to identify possible relationships among the items. Results Five themes, or factors, were found to categorize the perceptions of health: 1) lifestyles, 2) barriers to healthy lifestyles, 3) personal responsibility, 4) self-care behaviors, and 5) culturally defined well-being. Two factors classified the perceptions of diabetes: 1) a cognitive factor, related to personal experience, and 2) an affective factor, related to emotions. Conclusion Our diabetes assessment tool identified factors that should be considered when developing health promotion and diabetes prevention programs for American Indians. A valid assessment tool for the American Indian population could provide valuable, formative data that would increase understanding of the culturally related obstacles to health promotion and diabetes prevention.